The Role of Immune Cells in Post-Stroke Angiogenesis and Neuronal Remodeling: The Known and the Unknown - Ma, Yinzhong; Yang, Shilun; He, Qianyan; Zhang, Dianhui; Chang, Junlei (Frontiers in Immunology, 2021)
Following a cerebral ischemic event, substantial alterations in both cellular and molecular activities occur due to ischemia-induced cerebral pathology. Mounting evidence indicates that the robust recruitment of immune cells plays a central role in the acute stage of stroke. Infiltrating peripheral immune cells and resident microglia mediate neuronal cell death and blood-brain barrier disruption by releasing inflammation-associated molecules. Nevertheless, profound immunological effects in the context of the subacute and chronic recovery phase of stroke have received little attention. Early attempts to curtail the infiltration of immune cells were effective in mitigating brain injury in experimental stroke studies but failed to exert beneficial effects in clinical trials. Neural tissue damage repair processes include angiogenesis, neurogenesis, and synaptic remodeling, etc. Post-stroke inflammatory cells can adopt divergent phenotypes that influence the aforementioned biological processes in both endothelial and neural stem cells by either alleviating acute inflammatory responses or secreting a variety of growth factors, which are substantially involved in the process of angiogenesis and neurogenesis. To better understand the multiple roles of immune cells in neural tissue repair processes post stroke, we review what is known and unknown regarding the role of immune cells in angiogenesis, neurogenesis, and neuronal remodeling. A comprehensive understanding of these inflammatory mechanisms may be helpful in identifying potential targets for the development of novel immunoregulatory therapeutic strategies that ameliorate complications and improve functional rehabilitation after stroke.